Complementary feeding indicators from the World Health Organization and the Ministry of Health: agreement analysis and comparison of estimated prevalence in a cohort of children in southwestern Bahia, Brazil, 2018 - Clessiane de Brito Barbosa; Elma Izze da Silva Magalhães; Daniela da Silva Rocha (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To assess the agreement between complementary feeding indicators established by the World Health Organization (WHO) and the Ministry of Health (MOH) and to compare the prevalence of these indicators in the first year of a child's life. Methods : This was a cross-sectional study in a cohort of 286 children from Vitória da Conquista, state of Bahia, Brazil; agreement between indicators and comparison between prevalences were analyzed using the Kappa coefficient and McNemar's test; the prevalence of the indicators "introduction of complementary feeding" (ICF), "minimum dietary diversity" (MDD), "minimum meal frequency" (MMF) and "minimum acceptable diet" (MAD) were calculated. Results : Three indicators showed poor agreement, with only one demonstrating moderate agreement; prevalence of WHO indicators was higher than that of the MOH (ICF, 94.3% vs. 20.7%; MDD, 75.2% vs. 50.7%; MMF, 97.2% vs. 44.8%; MAD, 96.8% vs. 26.9%). Conclusion The majority of indicators showed poor agreement and the prevalence of WHO indicators exceeded that of the Ministry of Health.